Strength training for athletes: does it really help sports performance? - McGuigan, M. R.; Wright, G. A.; Fleck, S. J. (International Journal of Sports Physiology and Performance, 2012)
The use of strength training designed to increase underlying strength and power qualities in elite athletes in an attempt to improve athletic performance is commonplace. Although the extent to which strength and power are important to sports performance may vary depending on the activity, the associations between these qualities and performance have been well documented in the literature. The purpose of this review is to provide a brief overview of strength training research to determine if it really helps improve athletic performance. While there is a need for more research with elite athletes to investigate the relationship between strength training and athletic performance, there is sufficient evidence for strength training programs to continue to be an integral part of athletic preparation in team sports.